Experience of Parenteral Administration of Methotrexate in a Female Patient Suffering from Early Juvenile Idiopathic Arthritis and Uveitis - Т. V. Sleptsova; Е. I. Alexeeva; Т. М. Bzarova; S. I. Valieva; R. V. Denisova; K. B. Isaeva; Е. G. Chistyakova; А. М. Chomakhidze; N. I. Taybulatov (Вопросы современной педиатрии)
Represented here is a case of early juvenile idiopathic arthritis associated with uveitis diagnosed in a three-year-old female patient subject to treatment with the standard methotrexate dosage. At the initial stage of treatment, the child demonstrated severe articular syndrome, inflammatory reactions affecting eyeball surfaces, increased laboratory indicators of the illness and functional insufficiency. Successful overcoming of methotrexate resistance through dosage increased up to 20 mg/m2 of body surface per week was described. Over three months of subcutaneous methotrexate treatment with a 15 mg/m2-per-week dose, the child showed milder joint exudation an, arthralgia, less lengthy morning stiffness, although there was no 50% improvement based on ACRpedi criteria, and uveitis was first recognized in the subactive phase. The dose was increased up to 20 mg/m2 per week. By the eighth week of methotrexate treatment, uveal inflammation reversed. Non-active phase and remission were detected in 6 and 12 months respectively. The remission has persisted for 6 years. No side effects have been observed throughout methotrexate treatment.